Sources of wheat production technical inefficiency among smallholder farmers in Northwestern Ethiopia: Beta regression approach - Birara Endalew; Mezgebu Aynalem; Adugnaw Anteneh; Habtamu Mossie (Cogent Economics & Finance, 2023)
Wheat production is dominated by a subsistence smallholder production system. Additionally, more than 4.7 million smallholder farmers are engaged in wheat production. However, poverty is chronic and pervasive among smallholder farmers. Hence, targeting the efficiency of wheat production is the right strategy to improve the well-being of smallholder farmers. Therefore, we conducted this study to measure the level of wheat production efficiency and figure out the sources of wheat production inefficiency among smallholder farmers using stochastic frontier and beta regression models, respectively. Hence, 400 smallholder farmers were selected to gather firsthand information on wheat production and important variables. The stochastic frontier result shows that the number of oxen, amount of urea fertilizer, and seed had a positive and statistically significant effect on the level of wheat production, unlike wheat farm size. The mean technical efficiency result indicates that smallholder farmers operate 23% below the maximum capacity of wheat production. Additionally, smallholder farmers were producing 18.97 quintals per hectare less than the potential production capacity. Consequently, the beta regression model result shows that an increase in the dependency ratio, distance to the local wheat market, and distance to the extension office will increase the technical inefficiency of wheat production. On the contrary, educational status, farm experience, and access to wheat price information decrease the technical inefficiency of wheat production. Therefore, policymakers, stakeholders, and farmers should consider the main sources of technical inefficiency to minimize the sources of wheat production inefficiency.
Keywords: 330; Beta regression; Debre Elias; stochastic frontier; technical inefficiency; wheat